Quantifying Protection Against Influenza Virus Infection Measured by Hemagglutination-inhibition Assays in Vaccine Trials. Issue 1 (January 2016) - Zhao, Xiahong; Fang, Vicky J.; Ohmit, Suzanne E.; Monto, Arnold S.; Cook, Alex R.; Cowling, Benjamin J.
Abstract : Background: Correlations between hemagglutination-inhibition titers (hereafter "titers") and protection against infection have been identified in historical studies. However, limited information is available about the dynamics of how titer influences protection. Methods: Titers were measured in randomized, placebo-controlled vaccine trials in Hong Kong among pediatrics during September 2009–December 2010 and the United States among adults during Oct 2007–April 2008. Intermediate unobserved titers were imputed using three interpolation methods. As participants were recruited at different times leading to varying exposure to infection relative to entry, a modified proportional hazards model was developed to account for staggered entry into the studies and to quantify the correlation of titers with protection against influenza infections, adjusting for waning in titers. The model was fitted using Markov chain Monte Carlo and importance sampling. Results: A titer of 1:40 was associated with a reduced infection risk of 40%–70% relative to a titer of 1:10, depending on the circulating strain; the corresponding protection associated with a titer of 1:80 was 54%–84%. Results were robust across interpolation methods. The trivalent-inactivated vaccine reduced cumulative incidence of influenza B and influenza A(H3N2) infections by six percentage points (pp; 95% credible interval = 2 pp, 10 pp) and 1 pp (95% credible interval = 0.3 pp, 2 pp) respectively, but not for influenza A(H1N1)pdm09. The live-attenuated vaccine showed little efficacy against influenza A(H3N2) infections. Conclusions: Titers are correlated with protection against influenza infections. The trivalent inactivated vaccine can reduce the risk of influenza A(H3N2) and influenza B infections in the community. Abstract : Supplemental Digital Content is available in the text.